2009
DOI: 10.1103/physrevb.80.033404
|View full text |Cite
|
Sign up to set email alerts
|

Tunable band gap and magnetic ordering by adsorption of molecules on graphene

Abstract: We have studied the electronic and magnetic properties of graphene and their modification due to the adsorption of water and other gas molecules. Water and gas molecules adsorbed on nanoscale graphene were found to play the role of defects which facilitate the tunability of the bandgap and allow us to control the magnetic ordering of localized states at the edges. The adsorbed molecules push the wavefunctions corresponding to α-spin (up) and β-spin (down) states of graphene to the opposite (zigzag) edges. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(62 citation statements)
references
References 29 publications
2
58
0
Order By: Relevance
“…This makes all the zigzag GNRs metallic. Again calculations based on Discrete Fourier Transforms (DFT) show that armchair nanoribbons are semiconducting with an energy gap scaling with the inverse of the GNR width [1]. Research showed that decreasing GNR width increases energy band gaps [8].…”
Section: Graphene Nanoribbonsmentioning
confidence: 99%
See 2 more Smart Citations
“…This makes all the zigzag GNRs metallic. Again calculations based on Discrete Fourier Transforms (DFT) show that armchair nanoribbons are semiconducting with an energy gap scaling with the inverse of the GNR width [1]. Research showed that decreasing GNR width increases energy band gaps [8].…”
Section: Graphene Nanoribbonsmentioning
confidence: 99%
“…1 Graphene is a 2D building material for carbon materials of all other dimensionalities. [1] Technically, 7 -graphene is a crystalline allotrope of carbon with 2-dimensional properties. It can be described as a one-atom thick layer of graphite.…”
Section: Basic Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…But the realization of halfmetallicity is practically difficult, because a very high critical transverse electric field is needed to break the spin degeneracy. Many researchers have suggested various methods to break the spin degeneracy, [9][10][11][12][13][14][15][16][17][18][19][20] and they successfully showed the half-metallicity without applying the external electric fields. Kan et al 9 proposed a chemical decoration technique to realize half-metallicity in the ZGNRs.…”
mentioning
confidence: 99%
“…Berashevich et al found that the dipoles of water and other molecules can also push the wave functions spin-up and spin-down to the opposite direction. 20 The isosurface of the charge density difference between the spin-up and the spin-down channels is displayed in Fig. 2(b).…”
mentioning
confidence: 99%